Over the "middlebrow" to the "midcult" - Vrajová, Jana (Bohemica Olomucensia, 2014)
The study deals with the genesis of the term midcult. It shows, how was the term used by Dwight Macdonald, Virginia Woolf and Umberto Eco. Macdonald's thinking was primarily based on cultural and sociological thinking working with ideas of marxism. Nor for Virginia Woolf was or essential to specify the distinctive features of literature for middlebrows, she preferes to describe the level of intellectual prestige senders. Due to societal changes that have taken place since the publication of both texts and which lead to the permeability of different social strata, it seems to be more productive to think about midcult following to Eco's semiotic concepts.